Twin momentum: Fundamental trends matter - HUANG, Dashan (Institutional Knowledge at Singapore Management University, 2017)
Using both the levels and the time-series trends of a collection of firms' major fundamentals, we find that fundamentals matter after all: they can also generate strong return momentum. A fundamental momentum strategy that goes long stocks with fundamental in the top quintile and short stocks with fundamental in the bottom quintile earns a monthly average return of 88 bps, and is comparable with the popular price momentum but has little correlation. Combining price momentum and fundamental momentum yields a twin momentum, which has an average return more than the sum of both price momentum and fundamental momentum. Twin momentum cannot be spanned by extant risk factor models, nor can it be explained by short-sale impediments and investor sentiment.